(untitled) (Scientific journal of the Fergana State University, 2023)
This article describes how to solve a rectangular triangle with only one hypotenuse, or to solve all of its second catheters and hypotenuse, and to solve all three-dimensional equations when given the diagonal length of a rectangular parallel.